Comparative Legal Study on the Death Penalty for Corruption Crimes in China and Indonesia - Retno Nurkumala; Kristi Warista Simanjuntak; A. Sakti R.S. Rakia (Journal of Law Justice (JLJ), 2026)
This study aims to explore research focused on a comparison between the legal systems of China and Indonesia and to assess the effectiveness of the death penalty as a deterrent against corruption, with the goal of improving the legal system in Indonesia. The method used in this study is quantitative analysis.  The novelty of this research lies in the reformulation of indicators for the application of the death penalty, which are no longer general in nature but must be based on a classification of the severity of corruption, integrated through a comprehensive analysis of actus reus and mens rea. This is reinforced by Article 28J of the 1945 Constitution, which states that an individual’s human rights may be limited by the obligation to respect the rights of others in order to maintain public order. Although Indonesia has taken an abstentionary stance in international forums such as Amnesty International, domestic law still permits the imposition of the death penalty. The results of the study indicate that Article 2, paragraph (2) of the Anti-Corruption Law does not provide legal certainty regarding the application of the death penalty for perpetrators of corruption. Based on data from ICJR and Amnesty International for 2024, it is evident that no corruption offenders have been sentenced to death in Indonesia; conversely, the death penalty is more frequently imposed in drug-related and murder cases. This lack of law enforcement has allowed a culture of corruption to flourish, necessitating a more progressive theoretical approach so that the law can become more flexible and responsive in achieving substantive justice. The conclusion is that, as an alternative to addressing human rights issues, the National Criminal Code (Law No. 1/2023) offers a compromise by establishing the death penalty as a sanction subject to a 10-year probationary period and a clemency procedure. This approach is considered a fair means of upholding the principle of “fiat justitia ruat coelum” (let justice be done though the heavens fall) while still taking humanitarian values into account.